Investigation of mechanical properties and proton irradiation behaviors of SA-738 Gr.B steel used as reactor containment. (August 2016) - Ma, Yongzheng; Ran, Guang; Chen, Nanjun; Lei, Penghui; Shen, Qiang
Highlights: The mechanical properties and microstructure of as-received steels were analyzed. At the unirradiated conditions, SA-738Gr.B steels had high tensile strength and excellent impact fracture toughness, which met the performance requirements of ASME codes. The irradiation behaviors of SA-738Gr.B steel were investigated after irradiation with 400 keV proton from 0.2 dpa to 1 dpa at 150 ºC. Irradiation defect density and mean positron lifetimes increased with increasing of displacement damage. The stress-relief annealing treatment improved the ability of irradiation resistance that based on open volume defect analysis from proton irradiation. Abstract: The proton irradiation behaviors of two kinds of SA-738Gr.B steels prepared by different heat treatment used as AP1000 reactor containment were investigated by transmission electron microscopy and positron annihilation lifetime spectrum (PAS). The mechanical properties of as-received steels were also measured. In the unirradiated conditions, the SA-738Gr.B steels had high tensile strength and excellent impact fracture toughness, which met the performance requirements of ASME codes. Both kinds of SA-738Gr.B steels were irradiated by 400 keV proton from 1.07 × 10 17  H + /cm 2 to 5.37 × 10 17  H + /cm 2 fluence at 150 ºC. Some voids and dislocation loops with several nanometers were observed in the cross-section irradiated samples prepared by electroplating and then twin-jet electropolishing technology. The number of irradiation defects increased with increasing of displacement damage, as well as for the mean positron lifetimes. The stress-relief annealing treatment improved irradiation resistance based on open volume defect analysis from proton irradiation. SA-738Gr.B (SR) steel had higher proton irradiation resistance ability than that of SA-738Gr.B (QT) steel. The mechanism of irradiation behaviors were also analyzed and discussed.